Pengaruh Green Innovation, Digital Marketing, Dan Market Orientation Terhadap Keunggulan Kompetitif. ( Studi Pada Konsumen Batik Olive Kota Batu ) - Levy Marisda Sari; Khalikussabir Khalikussabir; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the effect of Green Innovation, Digital Marketing, and Market Orientation on Competitive Advantage at consumers Batik Olive in Kota Batu. This research employs a quantitative approach with an explanatory research design. The sample consists of 85 respondents who are consumers of Batik Olive Kota Batu, selected using a purposive sampling technique. Primary data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26.0. The results simultaneously indicate that Green Innovation (X1), Digital Marketing (X2), and Market Orientation (X3) have a significant effect on Competitive Advantage (Y). Partially, Digital Marketing and Market Orientation have a positive and significant influence on Competitive Advantage, while Green Innovation does not have a significant effect on the Competitive Advantage of UMKM Batik Olive Kota Batu. These findings suggest that the improvement of Batik Olive’s competitiveness is more dominantly influenced by the optimization of digital marketing strategies and market orientation compared to the implementation of green innovation, which has not yet been fully integrated strategically. Keywords: Green Innovation; Digital Marketing; Market Orientation; Competitive Advantage; batik MSMEs.